Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja Pegawai pada Kantor Kecamatan Babelan - Nia Nurfitri (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine how much Leadership and Work Environment affect Employee Job Satisfaction at the Babelan District Office. The population in this study were all employees of the Babelan District Office. This study uses a quantitative method. Data collection through distributing questionnaires to 52 respondents. This sampling technique uses the census technique method. The results of this study indicate that the leadership variable has a partial effect (t-test) with the results showing that leadership has a positive and significant effect on employee job satisfaction with the results obtained t count of 5.092> t table 2.01063, the work environment variable has a partial effect (t-test) with the results showing that the work environment has a negative and significant effect on employee job satisfaction with the results obtained t count of -2.261 <t table 2.01063. Based on the results of the simultaneous F Test, the calculated F value is 14.765 > 2.79 with a Sig. value of 0.000 < 0.05 or a significant value less than 0.05. Therefore, Ho is rejected or Ha is accepted, which indicates that the variables of leadership and work environment have a high influence on employee job satisfaction.